Vitamin C supplementation does not influence plasma and blood mononuclear cell IL-6 and IL-10 levels after exercise - Aguilóa, A.; Monjob, M.; Morenoa, C.; Martineza, P.; Martineza; Taulerc, P. (Journal of Sports Sciences, 2014)
The aim of this study was to determine whether the highest vitamin C supplementation associated with complete bioavailability influences the plasma and blood mononuclear cell IL-6 and IL-10 response to exercise. A double-blinded study of supplementation with vitamin C was performed. After 15 days of supplementation with vitamin C (500 mg/day, n = 16) or a placebo (n = 15), participants in the study completed a 15-km run competition. Blood samples were taken before and after competition. Oxidative stress markers, antioxidants, cortisol, IL-6 and IL-10 were determined in plasma or serum. IL-6 and IL-10 protein and mRNA levels were measured in blood mononuclear cells. Although higher plasma and blood mononuclear cell vitamin C levels were observed in the supplemented group when compared with the placebo one, the two groups showed identical exercise-induced changes in all the measured parameters. Exercise induced increased IL-6 and IL-10 levels in plasma and blood mononuclear cells. IL-6 and IL-10 mRNA levels in blood mononuclear cells increased after the competition. After recovery, IL-6 mRNA returned to basal levels and IL-10 mRNA levels remained elevated. In conclusion, exercise induced increased IL-6 and IL-10 production in blood mononuclear cells. However, vitamin C supplementation did not influence IL-6 and IL-10 response to exercise.